1988
DOI: 10.1038/jcbfm.1988.140
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Accumulation during the Evolution of Hypoxic—Ischemic Brain Damage in the Immature Rat

Abstract: Summary: An excessive accumulation of calcium in neu ronal and other tissues has been postulated to represent a "final common pathway" for cell death arising from hyp oxia-ischemia. To clarify the role of altered calcium flux into and distribution within the perinatal brain under going hypoxic-ischemic injury, 7-day postnatal rats un derwent unilateral common carotid artery ligation fol lowed by 3 h of hypoxia with 8% oxygen. This insult is known to produce brain damage confined to the cerebral hemisphere ipsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…However, any interpretation of the observed responses must take into account the effects of maturation and the effects of hypoxic ischemic injury, specifically the biochemical changes associated with reperfusion injury. [45][46][47] Any interpretation of the identified hemodynamic responses in these infants is clearly subject to multiple confounding factors. In addition to HIE itself, TH and anticonvulsant treatments also contribute to the presence of a pathological EEG trace, and are also likely to affect neurovascular coupling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, any interpretation of the observed responses must take into account the effects of maturation and the effects of hypoxic ischemic injury, specifically the biochemical changes associated with reperfusion injury. [45][46][47] Any interpretation of the identified hemodynamic responses in these infants is clearly subject to multiple confounding factors. In addition to HIE itself, TH and anticonvulsant treatments also contribute to the presence of a pathological EEG trace, and are also likely to affect neurovascular coupling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the striatum, damage is maximal medially towards the ependyma of the lateral ventricle; in the thalamus, damage is always focal and usually limited to the lateral half. In other studies, we have shown columnar alterations in NADH fluorescence (as a reflection of the cellular oxidation-reduction state) and in the accumulation of radiolabelled Ca++ in the same location of cerebral cortex and hippocampus as histologically verified tissue damage (12,32). As with alterations in regional cerebral blood flow (33), pertubations in rCGU per se do not appear to predict the heterogeneous pattern of damage seen within individual structures of the brain.…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively, excitatory neurotransmitters affect ischemic neuronal injury in an age-dependent fashion 19 - 20 and may contribute to the age-related differences in ischemic outcome that we observed. Prostanoids and calcium fluxes have been implicated in the regulation of CBF 21 and the evolution of ischemic brain injury 22 in immature brain and may explain the age-dependent effects of ischemia.…”
Section: Discussionmentioning
confidence: 99%